Bombs after the presidential election: slowing Indonesia's rise? - Yang Razali Kassim (2016)
Twin terrorist bomb attacks on two hotels in Jakarta in the morning of 17 July ushered in Yudhoyono’s second term as president. Will this development shake his confidence or strengthen his resolve to lead Indonesia back to its role as a key player in the region?